Gene Electrotransfer of Plasmid with Tissue Specific Promoter Encoding shRNA against Endoglin Exerts Antitumor Efficacy against Murine TS/A Tumors by Vascular Targeted Effects. - Monika Stimac (PLoS ONE, 2015)
Vascular targeted therapies, targeting specific endothelial cell markers, are promising approaches for the treatment of cancer. One of the targets is endoglin, transforming growth factor-β (TGF-β) co-receptor, which mediates proliferation, differentiation and migration of endothelial cells forming neovasculature. However, its specific, safe and long-lasting targeting remains the challenge. Therefore, in our study we evaluated the transfection efficacy, vascular targeted effects and therapeutic potential of the plasmid silencing endoglin with the tissue specific promoter, specific for endothelial cells marker endothelin-1 (ET) (TS plasmid), in comparison to the plasmid with constitutive promoter (CON plasmid), in vitro and in vivo. Tissue specificity of TS plasmid was demonstrated in vitro on several cell lines, and its antiangiogenic efficacy was demonstrated by reducing tube formation of 2H11 endothelial cells. In vivo, on a murine mammary TS/A tumor model, we demonstrated good antitumor effect of gene electrotransfer (GET) of either of both plasmids in treatment of smaller tumors still in avascular phase of growth, as well as on bigger tumors, already well vascularized. In support to the observations on predominantly vascular targeted effects of endoglin, histological analysis has demonstrated an increase in necrosis and a decrease in the number of blood vessels in therapeutic groups. A significant antitumor effect was observed in tumors in avascular and vascular phase of growth, possibly due to both, the antiangiogenic and the vascular disrupting effect. Furthermore, the study indicates on the potential use of TS plasmid in cancer gene therapy since the same efficacy as of CON plasmid was determined.